Aqueous Dispersions of Graphene from Electrochemically Exfoliated Graphite. Issue 48 (24th October 2016) - Sevilla, Marta; Ferrero, Guillermo A.; Fuertes, Antonio B.
Abstract: A facile and environmentally friendly synthetic strategy for the production of stable and easily processable dispersions of graphene in water is presented. This strategy represents an alternative to classical chemical exfoliation methods (for example the Hummers method) that are more complex, harmful, and dangerous. The process is based on the electrochemical exfoliation of graphite and includes three simple steps: 1) the anodic exfoliation of graphite in (NH4 )2 SO4, 2) sonication to separate the oxidized graphene sheets, and 3) reduction of oxidized graphene to graphene. The procedure makes it possible to convert around 30 wt % of the initial graphite into graphene with short processing times and high yields. The graphene sheets are well dispersed in water, have a carbon/oxygen atomic ratio of 11.7, a lateral size of about 0.5–1 μm, and contain only a few graphene layers, most of which are bilayer sheets. The processability of this type of aqueous dispersion has been demonstrated in the fabrication of macroscopic graphene structures, such as graphene aerogels and graphene films, which have been successfully employed as absorbents or as electrodes in supercapacitors, respectively. Abstract : Break it up ! A facile and high‐yield approach is presented to prepare aqueous graphene dispersions based on the electrochemical exfoliation of graphite (see figure). The processability of the graphene dispersion was demonstrated in the fabrication of aerogels and films, which have been employed as absorbents and as electrodes in supercapacitors, respectively.